Exploring Task-Specific Independent Standing in 3- to 5-Month-Old Infants - Sigmundsson, Hermundur; Lorås, Håvard W; Haga, Monika (Frontiers in Psychology, 2017)
Perspectives on developmental milestones suggest that an infant’s ability to stand without support occurs at the age of 9-16 months. The two exploratory tasks were part of a baby swimming routine, conducted over a period of 12 weeks (24 sessions), and the aim was to examine whether young infants (mean age 97 days) improved their performance in standing as measured by prolonged time-to-stand. The data suggest that 3-5 month old infants are capable of demonstrating signs of motor learning in task-specific standing. The results appear remarkable when compared to the expected age required for other forms of independent standing, The developmental process of independent standing is discussed in relation to the complex interaction between genetic and environmental factors